Multiscale modelling of granular materials in boundary value problems accounting for mesoscale mechanisms. (June 2021) - Wautier, A.; Veylon, G.; Miot, M.; Pouragha, M.; Nicot, F.; Wan, R.; Darve, F.
Abstract: The proper solution of geotechnical boundary value problems requires robust constitutive models that can describe the mechanical behavior of geomaterials under various loading conditions, while also accounting as closely as possible for the different material scales of interest. This is even more relevant to granular media where the complexity of the mechanical behaviour is not limited to the nature of the contact law between grains, and instead originates from the multiplicity of contacts oriented along all the directions of the physical space to form distinctive mesostructures. This paper revisits the so-called H-model, which belongs to the broad family of micromechanical approaches whereby an intermediate scale (mesoscale) is explicitly introduced into the formulation. One great advantage of the model is that it can be extended by accounting for further multi-physical couplings, as for example the presence of capillary bridges between grains. This versatile model was implemented within an explicit finite difference based computational software (FLAC), and the present work demonstrates its ability to analyze engineering problems with a microstructural viewpoint, while also providing new insights in microstructural mechanisms of failure difficult to capture with standard phenomenological models.